The Identification of Gelatin source in Toothpaste products using Combination of Attenuated Total Reflection-Fourier Transform Infrared (ATR-FTIR) Spectroscopy and Chemometrics - Roswiem, Anna P.; Mustaqimah, Dewi N. (International Journal of Halal Research, 2020)
Toothpaste products traded within Indonesia are produced locally and internationally. Some of the toothpaste products may contain gelatin, a protein derived from bovine or porcine skin and bones. There are only few researchers studying gelatin in the toothpaste. Therefore, this study aimed to examine the presence of gelatin in toothpaste using the Attenuated Total Reflectance-Fourier Transform Infrared (ATR-FTIR) spectroscopy method combined with chemometrics. The presence of gelatin in the sample was identified from the similarity of the infrared spectrum profile between the sample and the standard gelatin of cow and pig origins. The spectra data sets from ATR-FTIR were subject to Principal Component Analysis (PCA) and subsequent Soft Independent Modeling of Class Analogy (SIMCA) method to precisely classify the origin of the gelatin. The study showed that the ATR-FTIR method can be used to identify the presence of gelatin in toothpaste products. Gelatin was detected in two out of 42 samples. However, the combination of the ATR-FTIR technique with chemometry could not provide excellent illustration of the origin of gelatin in the toothpaste products. We presumed that the gelatin was only added in small amounts in these samples to serve as a stabilising or emulsifying agent.